CASTRO-GÓMEZ, S. (2022). La rebelión antropológica. El joven Karl Marx y la izquierda hegeliana (1835-1846). Madrid: Siglo XXI España - Garbarino, Maximiliano Alberto (Daimon Revista Internacional de Filosofia, 2025)
Reseña de CASTRO-GÓMEZ, S. (2022). La rebelión antropológica. El joven Karl Marx y la izquierda hegeliana (1835-1846). Madrid: Siglo XXI España